Determinant Factors in Purchasing Decisions on Uncertified Halal Food Products: Study on Indonesian Students in Taiwan - Pratiwi, Viera Nu'riza; Putri, Endah Budi Permana; Rahajeng, Sa'bania Hari; Viantry, Paramita; Ramadhana A.B., Rakha (UIN Sunan Gunung Djati Bandung, 2024)
This research investigates the determinant factors influencing the purchasing decisions of Indonesian students in Taiwan regarding uncertified halal food products. Despite the growing demand for halal products globally, the uncertainty surrounding the halal status of certain food items poses challenges, particularly for Muslim consumers. This study focuses on Indonesian students in Taiwan due to their unique position as international students residing in a country where halal certification may be less prevalent compared to their home country. Data was collected via structured questionnaires distributed among Indonesian students in various universities across Taiwan through a quantitative approach. The study employed multiple regression analysis to examine the relationships between several key variables, including trust, halal awareness, perceived behavioral control, subjective norms, religiousness and attitudes toward purchasing uncertified halal food products. The findings reveal significant insights into the factors influencing purchasing decisions in this context. Trust emerges as a crucial factor, indicating that consumers' confidence in the halal status of products, despite lacking certification, significantly influences their purchasing attitudes. Furthermore, perceived behavioral control plays a significant role, reflecting individuals' perceived ability to access and acquire uncertified halal products. Subjective norms also demonstrate a notable impact, reflecting the influence of social expectations and support from important reference groups. Interestingly, religiousness does not emerge as a significant determinant, suggesting that other factors may overshadow its influence in this context. Trust and perceived behavioral control significantly influence purchasing attitudes and decisions toward uncertified halal food products. In contrast, religiosity and halal awareness have less impact, suggesting the need for further research into additional factors that shape consumer behavior.